Improving the Treatment Process of Bengali Autistic Children using Specialized Mobile Application - Rashid Al SHAFEE; Rakibul HUDA; Mohammad Imran HOSSAIN; Md.Mahmudul Hasan SHOHAG; Shahidul Islam KHAN (Database Systems Journal, 2023)
Many children in Bangladesh have ASD. The rate of Autism Spectrum Disorder (ASD) is increasing in Bangladesh and other countries, day by day. Autistic children find it difficult to talk and express themselves regarding what they want or not. Also, some autistic children are not comfortable dealing with the outside world. For example, they do not feel comfortable in social settings or in any program. There are some schools and organizations where many kind-hearted people are trying to help those autistic children in many ways. We all know that there is no cure for autism. But it can be reduced. After good treatment, an autistic child can recover. To help the treatment process, we have developed an interactive app that will help them to cope with social events and places, as well as help them with verbal tasks. We have developed a model to access the severity of an autistic child and help the child to improve communication. This paper presents our interactive app and also provides a concise comparison of it with existing apps to support children with ASD.